Fourteen-Year Long-Term Results after Gastric Banding - Christine Stroh; Ulrich Hohmann; Harald Schramm; Frank Meyer; Thomas Manger (Journal of Obesity)
Background. Gastric banding (GB) is a common bariatric procedure that is performed worldwide. Weight loss can be substantial after this procedure, but it is not sufficient in a significant portion of patients. Long-term rates for associated complications increase with every year of follow up, and only a few long-term studies have been published that examine these rates. We present our results after 14 years of postoperative follow up. Methods. Two hundred patients were operated upon form 01.02.1995 to 31.01.2009. Data collection was performed prospectively. In retrospective analysis, we analyzed weight loss, short- and long-term complications, amelioration of comorbidities and long-term outcome. Results. The mean postoperative follow up time was 94.4 months (range 2–144). The follow up rate was 83.5%. The incidence of postoperative complications for slippage was 2.5%, for pouch dilatation was 9.5%, for band migration was 5.5% and 12.0% for overall band removal. After 14 years, the reoperation rate was 30.5% with a reoperation rate of 2.2% for every year of follow up. Excess weight loss was 40.2% after 1 year, 46.3% after 2 years, 45.9% after 3 years, 41.9% after five years, 33.3% after 8 years, 30.8% after 10 years, 33.3% after 12 years and 15.6% after 14 years of follow up. Conclusion. The complication and reoperation rate after GB is high. Nevertheless, GB is still a therapeutic option in morbid obese patients, but the criteria for patient selection should be carefully evaluated.